Polityki innowacji w procesie europeizacji: od konceptualizacji do operacjonalizacji - Dyduch, Joanna (Uniwersytet Opolski, 2015)
The aim of the chapter is to analyse the europeanisation process of the innovation policy within the European Union (EU). The analysis contains reflection on the main dimensions of the Europeanisation processes in the investigated area. Moreover instruments and mechanisms of Europeanisation are going to be pointed out, described and explained. This will help to answer the question about the level of supranationalisation of the innovation policy and to forecast possible trends of its further development.
Keywords: innovation policy; innovations; Europeanisation; European Union